The Role Of Tea Tree Oil as A Skin Antimicrobial : A Literature Study - Dian Ardiana (UNUSA Press, 2021)
Background: Skin disease due to microorganism infection are still widely found in community. The infections can be caused by bacteria, viruses, fungi, and parasite. Tea tree oil often used as a herbal medicine in the treatment of skin diseases due to microorganisms. This literature study is conducted to review the role of tea tree oil as an antimicrobial in skin infections. Method: Fifteen indexed journals published from 2015 to 2020 about tea tree oil and skin infections, were included. From 15 journals, 9 journals discuss antibacterial activity of tea tree oil, 2 journals discuss antiviral activity, 9 journals discuss antifungal activity, and 1 journal discusses antiparasitic activity. All journals state that tea tree oil has an antimicrobial effect on microorganisms that cause skin infections. Result: From 9 journals, it was found that A. baumanni, P. aeruginosa, and C. acnes were the most sensitive bacteria to tea tree oil in terms of MIC and S. epidermidis was the most sensitive bacteria, seen from their inhibition zone. Eight journals state variations with significant differences in the activity of tea tree oil as an anti-fungal. Tea tree oil has stronger antibacterial activity than antifungal activity. It also has antiviral activity against HSV and antiparasitic on S. scabiei. Conclusion: The conclusion of this study is that tea tree oil has antimicrobial activity against microorganisms that cause skin disease, including bacteria, viruses, fungi, and parasite.